2022
DOI: 10.5808/gi.22067
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance in Klebsiella pneumoniae: identification of bacterial DNA adenine methyltransferase as a novel drug target from hypothetical proteins using subtractive genomics

Abstract: Klebsiella pneumoniae is a gram-negative bacterium that is known for causing infection in nosocomial settings. As reported by the World Health Organization, carbapenem-resistant Enterobacteriaceae, a category that includes K. pneumoniae, are classified as an urgent threat, and the greatest concern is that these bacterial pathogens may acquire genetic traits that make them resistant towards antibiotics. The last class of antibiotics, carbapenems, are not able to combat these bacterial pathogens, allowing them t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…S2). These results strongly suggest that G5K serves as a novel and promising broad-spectrum target for M. oryzae, being conserved across over 40 different pathogens (Mondal et al, 2015;Hossain et al, 2017;Cesur et al, 2020;Omeershffudin and Kumar, 2023).…”
Section: Discussionmentioning
confidence: 75%
“…S2). These results strongly suggest that G5K serves as a novel and promising broad-spectrum target for M. oryzae, being conserved across over 40 different pathogens (Mondal et al, 2015;Hossain et al, 2017;Cesur et al, 2020;Omeershffudin and Kumar, 2023).…”
Section: Discussionmentioning
confidence: 75%
“…The subcellular localization was identified using PsortB 3.0 [ 37 ]. Proteins localized in the cytoplasm are viable drug targets, while membrane proteins are often targeted as vaccine candidates [ 12 ]. Membrane proteins are likely to secrete antigenic proteins that the immune system can detect, which is why they are preferred as potential vaccine candidates [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Target alteration or reduction of target affinity is one of the critical resistance mechanisms in N. gonorrhoeae. In a recent study, the bacteria were found to develop resistance against extended-spectrum cephalosporin, cefixime, and ceftriaxone [8][9][10][11]. Cefixime is also no longer recommended as a first-line regimen [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations